JURIDICAL ANALYSIS ON COPYRIGHT LAW: THE NEW WAY OF ROYALTY DISTRIBUTION IN INDONESIA - Handiriono, Raden; Hasibuan, Fauzie Yusuf; Syarief, Elza (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The massive rise of technology, have changed the habit of copyright owner to earn them economic rights and moral rights, they hope to earn, especially the economic right often failed miserably, clearly there’s a huge problem between theoretically and reality about so called Royalty distribution that held economic matters to the copyright owners. This research have been made to find out the regulation of royalty distrubuton in Indonesia, and the second one is to find out the new model or the new way of royalty distribution In Indonesia, the methods of this research is Juridical Normative, which is bold to secondary data as main data, such as regulations, books and journal. Combined with primary legal materials, secondary legal materials to ensure the right method of this research, In this study, the approach method used is normative juridical The results of this study give bright proof that the regulation of the royalty distribution in Indonesia still exists until today, the copyright law and more special regulation in government regulation already give us protection and definition of royalty itself, unfortunately the problem is not only the regulation but also about the law enforcement and the Government efforts, For example there are too many institutions that have the right to collect and distribute the royalty as an economic rights, this one problem made copyright owner feel unsure about the collection of the royalty. Royalty as one of the economic rights, have big roles in the Copyright law, years after years the problem of royalty, especially royalty distribution in Indonesia cant be hide. To overcome this problem, the regulation itself cannot be the only one weapon that government have. Technology and information are supposed to be the answer of this problem, collaboration between government and private parties are the only way to solve this major problem.